The Influence of Internet Access Availability on Student Participation in Online Learning in Aceh Province - Raihani, Ayu; Mahliati (Lembaga KITA, 2024)
The purpose of the study: To analyze the effect of the availability of internet access on student participation in online learning in Aceh Province. The quantitative method was utilized, and data were collected using a survey method on 400 high school students in different provinces. Internet access availability, according to the findings of the analysis, has a significant positive effect on student participation in online learning (p <0.05). In this case a beta (β1) value of 0.65 implies that for every one unit increase in internet access availability, the model predicts a 0.65 unit increase in student participation. The R² = 0.42 means that the availability of internet access accounts for 42% of the variation in student participation. Moreover, students who are using internet greater than 10 Mbps participated more on comparison to students on internet between 1-10 Mbps or below 1 Mbps. This research further emphasizes the role of parental encouragement and schools' preparedness in determining student participation. The results point to the need for more initiatives to scale up internet access and speed in Aceh Province, particularly in rural and isolated regions, to support more equitable education outcomes. The results of this study are expected to be useful for policy makers in formulating policies and programs to improve internet access and quality of education in Aceh.Index Terms—Internet Access, Quality of Education, Aceh